"I remember when … ": The impact of reminiscence therapy on discourse production in older adults with cognitive impairment. (3rd May 2020) - Rose, Naomi; Whitworth, Anne; Smart, Sharon; Oliver, Elizabeth; Cartwright, Jade
Abstract: Purpose: Positive outcomes following reminiscence therapy have been reported for older adults with mild cognitive impairment and dementia in cognition and quality of life and, in a small number of studies, communication. Despite the close relationship between cognition and language, the impact on communication has received limited attention. This study aimed to investigate whether the spoken discourse of older adults with mild cognitive impairment or dementia could be improved within the genre of nostalgic recounts following group reminiscence therapy, and whether change generalised to everyday discourse. Method: Four females (mean: 87 years, SD: 7.3) who lived in a residential aged care facility and were diagnosed with mild ( n = 2) or major ( n = 2) neurocognitive impairment were recruited to attend a group reminiscence programme delivered in eight one-hour treatment sessions over four weeks. Multiple baseline samples of discourse were obtained in the week prior to intervention to monitor stability. Macrostructure, rate, informativeness and efficiency of discourse production were measured to identify change within nostalgic recounts and monitor evidence of generalised change in everyday discourse genres. Cognitive performance and quality of life were also monitored. Result: While variability was evident, significant increases in macrostructure and richness of nostalgic recounts were found for two participants, with significant generalisation to everyday discourse. Both participants had diagnoses of mild cognitive impairment. No significant improvements were seen in cognition or quality of life with all participants. Conclusion: This study provides promising evidence for the spoken recall of memories having the potential to improve the communication of people with neurocognitive disorders, with some indication that people with milder impairment may be more amenable to this form of intervention. Nostalgic recounts may provide an explicit context in which speech-language pathologists can facilitate the planning of spoken production in people with cognitive impairment, and influence speaking in everyday contexts.